2011
DOI: 10.1103/physrevlett.107.035004
|View full text |Cite
|
Sign up to set email alerts
|

Gyrokinetic Simulations of Solar Wind Turbulence from Ion to Electron Scales

Abstract: A three-dimensional, nonlinear gyrokinetic simulation of plasma turbulence resolving scales from the ion to electron gyroradius with a realistic mass ratio is presented, where all damping is provided by resolved physical mechanisms. The resulting energy spectra are quantitatively consistent with a magnetic power spectrum scaling of k(-2.8) as observed in in situ spacecraft measurements of the "dissipation range" of solar wind turbulence. Despite the strongly nonlinear nature of the turbulence, the linear kinet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
258
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(292 citation statements)
references
References 27 publications
33
258
1
Order By: Relevance
“…Several explanations have been proposed to explain the steeper scaling. For example, Howes et al (2011) also observed a k −2.8 ⊥ magnetic spectrum in their gyrokinetic simulations, interpreting the steeper-than-k −7/3 ⊥ result as due to the presence of electron Landau damping. The steeper spectrum, however, has also been observed in simulations that do not contain such damping Franci et al 2015).…”
Section: Phenomenological Models Of Kinetic Range Turbulencementioning
confidence: 99%
“…Several explanations have been proposed to explain the steeper scaling. For example, Howes et al (2011) also observed a k −2.8 ⊥ magnetic spectrum in their gyrokinetic simulations, interpreting the steeper-than-k −7/3 ⊥ result as due to the presence of electron Landau damping. The steeper spectrum, however, has also been observed in simulations that do not contain such damping Franci et al 2015).…”
Section: Phenomenological Models Of Kinetic Range Turbulencementioning
confidence: 99%
“…More recent theories of strong KAW turbulence also predict a -7/3 spectrum for both density and magnetic field (Schekochihin et al 2009). The fact that the observed spectra are typically steeper than this has been explained in several ways, including electron Landau damping (Howes et al 2011b), compressibility effect (Alexandrova et al 2007) and an intermittency correction resulting in a spectral index of -8/3 . The same spectral index of −8/3 can (Chen et al 2010a).…”
Section: Ion Scale Instabilities Driven By Solar Wind Expansion and Cmentioning
confidence: 99%
“…There is a range of terminology used to describe this range, including "dissipation range", "dispersion range" and "scattering range". The possible physics taking place here includes dissipation of turbulent energy (Leamon et al 1998(Leamon et al , 1999(Leamon et al , 2000Smith et al 2006;Schekochihin et al 2009;Howes et al 2011b), a further small scale turbulent cascade (Biskamp et al 1996;Ghosh et al 1996;Galtier 2006;Alexandrova et al 2007Schekochihin et al 2009;Howes et al 2011b;Rudakov et al 2011; or a combination of both.…”
Section: Turbulence At Kinetic Scalesmentioning
confidence: 99%
“…This formalism captures the large-scale fluctuations, compared to the proton thermal gyroradius. Although a kinetic approach is needed for the treatment of scales smaller than the proton gyroradius [1,2], where the interaction of kinetic Alfvén waves [3] and electron heating of the solar wind [4] become important, the self-organization of turbulent structures remains predominantly a large-scale effect, determined by fluidlike dynamics.In MHD turbulence, the conservation of cross helicity for the ideal systems represents a dynamical constraint of interest, as it is the quantity that leads to a balanced or imbalanced state of MHD turbulence. While the scaling of the energy spectra for these states has received a lot of attention in recent years [5][6][7], less effort was given to understand the impact on particle acceleration and heating due to the different arrangement of structures.…”
mentioning
confidence: 99%